Alhagi pseudalhagi Extract Exerts Protective Effects Against Intestinal Inflammation in Ulcerative Colitis by Affecting TLR4-Dependent NF-κB Signaling Pathways - Xiaoqin Xu; Xiaoqin Xu; Xiaoqin Xu; Juan Zhang; Liang Chen; Liang Chen; Liang Chen; Yu Sun; Degang Qing; Xuelei Xin; Xuelei Xin; Chunyan Yan (Frontiers Media S.A., 2021)
Alhagi pseudalhagi Desv. Extract (APE) is the major active fraction extracted from the aerial part of Alhagi pseudalhagi Desv. In view of its application in Uyghur medicine, it may be beneficial for the treatment of ulcerative colitis (UC). The aim of the present study was to investigate the possible beneficial effects of APE on UC mice and detect the possible mechanisms underlying these effects.Methods: An acute UC model was established in mice using dextran sulfate sodium. Sixty mice were randomly divided into six groups: normal, UC model, sulfasalazine (200 mg/kg), high-dose APE (APE-H, 2.82 g/kg), middle-dose APE (APE-M, 1.41 g/kg), and low-dose APE (APE-L, 0.70 g/kg) groups. Drugs were administered by gavage for 10 days after the induction of colitis. Serum and colon tissue samples were collected from the mice during the experiment, and survival signs, body weight changes, disease activity index (DAI), colon length, and colon wet weight in mice were determined after the treatment. UC-induced damage, including inflammation and ulceration of colon mucosa, were observed by the naked eye as well as using hematoxylin and eosin staining (H&E) and scanning electron microscopy and scored according to Wallace and Keean's criteria. We measured the levels of tumor necrosis factor α (TNF-α), interleukin (IL)-1β, IL-6, and IL-10 in the serum and colon tissues using ELISA. Additionally, the relative protein levels of toll-like receptor 4 (TLR4), nuclear factor-kappa B p65 (NF-κB p65), phosphorylated NF-κB p65 at Ser536 (p-p65 Ser536), inhibitor kappa B-kinase ß (IK-Kβ), and phosphorylated IK-Kβ (Ser176/180) (p-IK-Kβ) in colonic mucosal epithelial tissues were detected using western blotting. The main functional components of APE were analyzed and confirmed by UPLC-MS/MS.Results: APE treatment repaired the UC-induced colon mucosa injury, reduced the weight loss, attenuated DAI, colon macroscopic damage index, and histological inflammation, and significantly downregulated the levels of inflammatory markers, including TNF-α, IL-1β, and IL-6, in the serum and colon tissues. Additionally, APE treatment reduced the levels of TLR4 and phosphorylation of p-NF-κB and p-IK-Kβ. The main components of APE are taxifolin, 3,5-dihydroxy-2-(4-hydroxyphenyl)-7-[(2R,3R,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl) oxan-2-yl] oxychromen-4-one, hyperoside, rutin, kaempferol, isorhamnetin, 7,8-dihydroxyflavone, and kaempferide.Conclusions: To the best of our knowledge, the present study is first to demonstrate that APE exerts a protective effect against intestinal inflammation in UC by affecting TLR4-dependent NF-κB signaling pathways.